Association of Secondhand Smoke With Stroke Outcomes. Issue 11 (November 2016) - Lin, Michelle P.; Ovbiagele, Bruce; Markovic, Daniela; Towfighi, Amytis
Abstract : Background and Purpose—: Approximately half of never smokers are exposed to secondhand smoke (SHS). Smoking is a well-established stroke risk factor, yet associations between SHS, stroke, and poststroke mortality remain uncertain. We aimed to determine the prevalence of exposure to SHS among those with and without stroke and its impact on mortality. Methods—: Data were obtained from the US National Health and Nutrition Examination Surveys for 27 836 never smokers with/without self-reported stroke aged ≥18 years, sampled from 1988 to 1994 and 1999 to 2012, with linked mortality through 2010. Household exposure to SHS was determined by self-report; exposure severity was quantified by serum cotinine level. Independent relationships between SHS and all-cause mortality were assessed using Cox regression models, before and after adjusting for sociodemographics and comorbidities. Results—: From 1988 to 1994 to 1999 to 2012, age-adjusted prevalence of exposure to SHS declined from 11.5% to 6.6% among survivors of stroke ( P =0.08), and 14.6% to 5.9% among persons without stroke ( P <0.01). Factors associated with high exposure to SHS were male sex, black race, ⩽12th-grade education, poverty income ratio ⩽200%, high alcohol intake, and history of myocardial infarction (all P <0.05). High exposure to SHS was associated with higher odds of previous stroke (odds ratio, 1.46; P =0.026). There was a dose-dependent relationship between exposure to SHS and all-cause mortality after stroke. Conclusions—: Individuals with previous stroke have 50% greater odds to have been exposed to SHS; SHS is associated with a 2-fold increase in mortality after stroke. This study highlights the importance of obtaining exposure to SHS history and counseling patients and their families on the potential impact of SHS on poststroke outcomes. Abstract : Supplemental Digital Content is available in the text.